Dermal advanced glycation end-product accumulation is associated with sarcopenia-related measures in middle-aged and older men. (July 2022) - Matsumoto, Sayaka; Ochi, Masayuki; Akechi, Yuji; Takei, Satoko; Senzaki, Kensuke; Okada, Yoko; Miura, Shiroh; Ochi, Hirofumi; Igase, Michiya; Ohyagi, Yasumasa
Highlights: 'Sarcopenia' is the name given to the age-associated atrophy of muscles. We investigate the relationship between AGE accumulation in the skin and sarcopenia. The dermal accumulation of AGEs was measured using skin autofluorescence (SAF). We found significant correlations between SAF and grip strength in the elderly men. SAF in the forearms represent a biomarker of the risk of sarcopenia in men. Abstract: Aims: Sarcopenia is the age-associated atrophy of muscles, and advanced glycation end-products (AGEs) accumulate in patients with age-associated diseases. We aimed to investigate the relationship between AGE accumulation in the skin and sarcopenia in middle-aged and older Japanese people. Materials and methods: We enrolled 240 participants in this cross-sectional study. The participants consisted of 120 men (mean age 68.8 ± 10.1 years) and 120 women (mean age 67.4 ± 9.0 years). The level of dermal AGE accumulation in the forearms was measured using skin autofluorescence (SAF) and many parameters associated with sarcopenia, including grip strength and thigh muscle cross-sectional area (CSA), were evaluated during medical check-ups at the Ehime University Hospital. Results: Grip strength and thigh muscle CSA were significantly higher in men than women, but mean SAF did not significantly differ between them. There were significant correlations of age, height, C-reactive protein, glycated hemoglobin, grip strength, and thigh muscle CSA with SAF in men, but only age in women. Multivariate analysis showed that SAF was significantly independently associated with low grip strength in men (β =−0.211, p =0.046). The men were then allocated to four groups according to their grip strength and thigh muscle CSA, and SAF was significantly higher in the lowgrip strength/low-thigh muscle CSA group than in the high-grip strength/high-thigh muscle CSA group (low/low group 2.25 ± 0.37 and high/high group 1.93 ± 0.36, p =0.001). Conclusions: SAF is associated with sarcopenia-related measures, especially grip strength, in middle-aged and older Japanese men, but not women.